If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2w + 3x = 0 Solving 2w + 3x = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-3x' to each side of the equation. 2w + 3x + -3x = 0 + -3x Combine like terms: 3x + -3x = 0 2w + 0 = 0 + -3x 2w = 0 + -3x Remove the zero: 2w = -3x Divide each side by '2'. w = -1.5x Simplifying w = -1.5x
| 7x+32+6x=9x+3x-62 | | 100=-16t^2+192t+30 | | 3x+140=400 | | 2w=3x | | 44.88=3.4(-3.4n+3) | | 3/4x=3/8(x-5)=1/4 | | 6x^2=20x-6 | | 10(-8+8n)-8= | | 11+10(p-10)=44+5(2p-11) | | 27b+(-4)=-814 | | 600+-4.5y+2y=425 | | 2y^2-7y+8y^2-6y= | | 27(w-972)=297 | | 2x-(18/x)=0 | | -4(3-5x)-4x= | | 63=9(d-84) | | z/8+73=82 | | 7x-3=(3/4(8x-12)) | | 5/x=11.3 | | 2y^2-7y+10=0 | | 9c+10c+2= | | 8a^2-4a=0 | | -17(t+315)=153 | | x/5=11.3 | | 2(t+12)=50 | | y=3x+8d | | 4x+5y=95 | | 9w-6=48 | | 100[0.07(z+9)]= | | 7(5x-7)+2=-35x+51 | | 78=2(v-11) | | 15.51-9.40x=x |